Morphological Study and Toxicity Assessment of Cultured Cyanobacteria from Fish Pond - Majit, Jasmina; Hassan, Ruhana; Samsur, Mohamad (2010)
Microcystis, a well known microcystin (hepatotoxin) producing cyanobacterium, was recently recorded as the dominant blue green algae bloom-forming in fish ponds at the Indigenous Fisheries Research and Production Center (IFRPC), Tarat, Serian. The strain was isolated and maintained in laboratory culture using BG11 medium for morphological and toxicity assessment. The cell growth was monitored by using a spectrophotometer at 678 nm in optical density measurement. At different growth stages, the characteristics of cells were observed under Light and Scanning Electron Microscope and classified as single cells, compact spherical colonies, daughter colonies formation and clathration of older colonies. For toxicity assessment, the cells were harvested in their late exponential phase of growth. Each strain was lyophilized and extracted using methanol to obtain the crude extract. Five different concentrations were tested in brine shrimp assay and the extracts were toxic with a LC50 of less than 50 μg/ml within 24 hrs administration. Mouse bioassay was administered by intraperitoneal injection of toxin extract into ± 20 g white mice. From both bioassays, the cells extractions contain toxins that indicate it could be a potential toxin producer species. Further analyses on toxin properties by using high performance liquid chromatography method could be considered in future studies.